Insights of Mixing on the Assembly of DNA Nanoparticles - Williams, Manda (My University, 2013)
Size is a crucial parameter in the delivery of nanoparticle therapeutics, affecting mechanisms such as tissue delivery, clearance, and cellular uptake. The morphology of nanoparticles is dependent both upon chemistry and the physical process of assembly. Polyplexes, a major class of non-viral gene delivery vectors, are conventionally prepared by vortex mixing, resulting in non-uniform nanoparticles and poor reproducibility. Better understanding and control of the physical process of assembly, and mixing in particular, will produce polyplexes of a more uniform and reliable size, optimizing their efficiency for laboratory and clinical use. "Mixing" is the reduction of length scale of a system to accelerate diffusion until a uniform concentration is achieved. Vortex mixing is poorly characterized and sensitive to protocols. Microfluidic systems are notable for predictable fluid behavior, and are ideal for analyzing and controlling the physical interaction of reagents on the microscale, realm where mixing occurs. Several microdevices for the preparation of DNA polyplexes are explored here. Firstly, the staggered herringbone mixer, a chaotic advection micromixer, is used to observe the effects of mixing time on nanoparticle size. Next, a novel device to surround the reagent flows with a sheath of buffer, preventing interaction with the walls and confining the complexation to a zone of lower, less variable shear and residence time, is used to demonstrate the role of shear in nanoparticle assembly. Lastly, uneven diffusion between ion pairs produces a small separation of charge at fluid interfaces; this short-lived electric field has a significant impact on the transport of DNA over the time scales of mixing and complexation. The effects of common buffers on the transport of DNA are examined for possible applications to mixing and complexation. These three investigations demonstrate the importance of the physical process in polyplex assembly, and indicate several important considerations in the development of new protocols and devices.
Thesis (Ph.D.)--University of Washington, 2013
Keywords: microfluidics; mixing; modeling; nanoparticles; nucleic acid therapeutics; Biophysics; Nanotechnology; bioengineering